Cell wall proteins of Kluyveromyces fragilis: Surface and emulsifying properties - Vasallo, María del Carmen (2006)
Yeast cell wall proteins were extracted from homogenized suspensions with 0.75 mol/l NaOH, yielding after precipitation at isoelectric pH a pale-brown sediment. Lyophilized sample was fractionated on Sephadex G-50 to yield three fractions (Fr 1, Fr 2 and Fr 3). Fr 1, which had the highest yields and protein content, showed the highest molecular weight and best surface properties. Fr 2 and Fr 3 were mainly composed by polysaccharide-protein complexes. Fr 1 was further subfractionated on Sephacryl S-300 to produce three fractions (Fr A, Fr B and Fr C). All subfractions, turned out to be highly foamy during evaporation. The highest yields were obtained for Fr A, which also showed the highest molecular weight. Fractions Fr 1 and their subfractions Fr B and Fr C exhibited good surface activity and high emulsifying activity. Emulsions prepared with these fractions were the most stable against creaming and coalescence. Fr 2 cream phase presented a gel-like behavior as a consequence of polysaccharides acting as thickening agents.